PHARMACOKINETICS, BIO-EQUIVALENCE AND TISSUE RESIDUES OF TWO ORAL COLISTIN FORMULATIONS IN BROILER CHICKENS - Soliman, Ahmed M.; Elbestawy, Ahmed Ragab; Ibrahim, Sherin (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The present study was carried out to investigate and provide an overview of the pharmacokinetics, bio-equivalence and tissue residues of colistin in two oral tested products, BAC-Liquido® (Interchemi Co.) and Coline-L® (Medmac Co.) in healthy broiler chickens. Methods: The comparative pharmacokinetics, bio-equivalence, blood and tissue residues of BAC-Liquido® and Coline-L® in broiler chickens was studied after oral administration of both products in a dose of 100.000 IU colistin base/kg. b. wt once daily for 5 consecutive days. Results: Colistin in both products obeyed a two compartments open model following I. V administration. The disposition kinetics of BAC-Liquido® and Coline-L® following oral administration of 100.000 IU colistin base/kg. b. wt revealed that the maximum blood concentration [Cmax.] were 5.10 and 4.95 µg/ml and attained at [tmax.] of 5.90 and 6.40 h, respectively. Colistin in BAC-Liquido® and Coline-L® was eliminated with half-lives [t1/2β] equal to 3.15 and 2.89 h, respectively. The mean systemic bioavailability of colistin in BAC-Liquido® and Coline-L® following oral administration in healthy chickens was 3.75 and 4.05%, respectively. The blood (µg/ml) and tissue (µg/g) residues of Coline-L® and BAC-Liquido® following repeated oral administrations showed that liver, kidney; lung, breast, and thigh muscles contained the limited colistin residues. Colistin in both preparations was completely disappeared from all tissues at 24 h following the last oral dose (except liver 48 h). Conclusion: It was concluded that Coline-L® is bioequivalent to BAC-Liquido® since Cmax test/Cmax reference and AUCtest/AUCreference ratios were 0.97 and 1.06, respectively. Chickens should not be slaughtered for human consumption within treatment and could be consumed after the discontinuation of the treatment (except liver, withdrawal time 48 h) of either BAC-Liquido® or Coline-L®. Keywords: Pharmacokinetics, Colistin, Broiler chickens, Bioavailability, Tissue residue.